2009
DOI: 10.1002/ccd.22074
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous retrieval of intravascular and intracardiac foreign bodies with a dedicated three‐dimensional snare: A 3‐year single center experience

Abstract: Our data confirm that different kinds of FBs lodging in different sites of the cardiovascular system can safely and efficaciously be percutaneously retrieved by utilizing a dedicated three-dimensional snare device. This, therefore, suggests that this minimally invasive intervention should be rapidly attempted, thus anticipating several serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…A number of retrieval techniques for intracoronary foreign bodies have been developed over the years, ranging from open chest surgery to minimally invasive approaches including the loop snare retrieval system that was used in this case [8]. Large studies of outcomes in this patient population are quite limited given the infrequent nature of these events and likely publication bias.…”
Section: Discussionmentioning
confidence: 95%
“…A number of retrieval techniques for intracoronary foreign bodies have been developed over the years, ranging from open chest surgery to minimally invasive approaches including the loop snare retrieval system that was used in this case [8]. Large studies of outcomes in this patient population are quite limited given the infrequent nature of these events and likely publication bias.…”
Section: Discussionmentioning
confidence: 95%
“…The transthoracic echocardiogram suggested that the needle lay close to the tricuspid valve but did not demonstrate any tricuspid regurgitation, which if present may have affected the type of surgery planned. Successful percutaneous retrieval of intracardiac and intravenous foreign bodies has been reported using Dormia baskets and three‐dimensional snares 9,10 . These studies reported retrieval success rates of 96.2% and 95.5%, respectively, with no documented complications.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported retrieval success rates of 96.2% and 95.5%, respectively, with no documented complications. Bonvini et al advocate that minimally invasive methods of retrieval of foreign bodies should be rapidly attempted 9 . However, due to the fact that the needle lay in the anteroposterior direction, it was decided that percutaneous retrieval of the needle could cause significant disruption to the tricuspid valve, and that the safest method of removal was open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Un- fortunately, with this rise has come an increase in the incidence of lost or embolized foreign bodies in the central and peripheral circulation. The true incidence of retained foreign bodies is unknown, however it is estimated at 0.1% to 1.5% [1,2]. Examples of retained objects include J-wire, stents, Swan-Ganz catheters and pacemaker leads.…”
Section: Discussionmentioning
confidence: 99%